Future search : getting the whole system in the room for vision, commitment, and action - Weisbord, Marvin Ross (BK business book., 2010)
Extensively revised and expanded, Future Search, which is the classic, definitive, bestselling book on one of most powerful methods for changing and improving all types of organizations and communities, includes a host of new tools, and three new chapters. If you want to do strategic planning, product innovation, quality improvement, organizational restructuring, or any other major change in a participative, whole system way, this book is your guide. Over 30,000 of the original edition sold.